The Influence of Self-Efficacy and Learning Independence on the Job Readiness of Informatics Education Graduates - Rizka Rizkianna; Agus Efendi; Dwi Maryono (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2025)
The research aims to understand the relationship between self-efficacy and independent student learning readiness among working students. The research methodology used a correlational study. The population that was used in the research was all students in the XII computer engineering program at SMK Muhammadiyah 1 Sukoharjo, covering 143 students. While the research sample of 72 students was obtained by a cluster random sampling method of sampling. Data collection in this research uses three that is scales of self-efficacy, scales of independent learning, and scales of readiness for work students that have been tested for validity and reliability. The result showed that self-efficacy and independent learning have a positive and significant relationship with readiness for work students, whether independent or simultaneous. These findings imply that strengthening self-efficacy and developing independent character are crucial for schools in improving graduates' work readiness for the workplace.